Health literacy and health among the elderly: status and challenges in the context of the Polish population aging process - Słońska, Zofia A.; Borowiec, Agnieszka A.; Aranowska, Anita E. (Anthropological Review, 2015)
Introduction: Poland is a country which is characterized by the process of population aging resulting in a dynamic growth of the old-age dependency ratio. Thus, along with the aging process, we can expect, both at the individual and at the societal level, the intensification of the problems related to coping with worsening health and social dependency of the growing number of the elderly. One of the most necessary action contributing to the prevention of the above-mentioned threats is the development of health literacy. Study aim: The aim of the study is to describe and analyze, in the context of the process of aging, the status, the structure and the role of health literacy among the elderly in Poland. Material and methods: The analyzed data come from the Polish part of the European Health Literacy population-based, cross-sectional survey (HLS-EU). Field work was carried out by the TNS OBOP Research Institute in July 2011. Data were collected in Polish by a standardized questionnaire, using a Computer Assisted Personal Interview (CAPI). Results and conclusions: Almost every second person in the Polish adult population aged 15+ (44,6%) had low health literacy(inadequate + problematic). First of all the oldest people aged 65+ were at risk of low health literacy. 61,3% of Poles aged 65+ had low levels of general health literacy and only 12% of excellent, in contrast to people aged 50 years and below where these percentages were 39.9% and 21.5% respectively. In the context of this unsatisfactory level of health literacy, particularly in the elderly and the intensifying process of aging in the Polish population, health literacy development should occupy a very high position on the political agenda.